Institutional and development issues in integrated water resource management of Saigon River - Sajor, E.; Thu, M. (SAGE Publications, 2009)
The article focuses on endogenous institutional factors in the water sector and the challenges and opportunities to an alternative integrated management approach in Vietnam, particularly in the context of its political legacy, current development goal, and Doi Moi reforms, using Saigon River as a case study. It investigates three institutional problem areas constituting major constraints to integrated water resources management (IWRM): (a) bureaucratic fragmentation and separatism, (b) top-downism negating multistakeholder participation, and (c) highly centralized administration. It also highlights how the goal of rapid industrialization and economic growth tends to marginalize environmental concerns in policies in water and river management. The authors argue that despite great incompatibilities of the legacy and present features of water-related institutions to IWRM, broader exogenous factors in the country can provide impetus to water institutional changes. These are the currently ongoing reforms of grassroots participation and decentralization as well as the country’s enhanced integration and cooperation with the international community, especially with development donor agencies.